PROBLEMATIKA GURU SEKOLAH DASAR SANTA ANGELA BADUNG DALAM PEMBELAJARAN DI MASA PANDEMI COVID-19. - Mau, Maria Genoveva (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2022)
Education in Indonesia is one of the areas affected by the COVID-19 pandemic.With the limitation of interaction, the Ministry of Education in Indonesia also issued apolicy, namely by closing schools and using technology to replace the teaching andlearning process (KBM) using a network system (online), distance learning (PJJ) andlearning from home (BDR). By using this online learning system, various problems arefaced by students and teachers. Starting from economic factors (students don't havegadgets), bad signals, lack of parental knowledge in digitizing learning, each of them isbusy at work and so on. This requires creativity and innovation in learning from a teacher.Creativity is a function of three main components: expertise, creative thinking skills andmotivation. Expertise consists of knowledge: technical, procedural and intellectual. Due to rapid technological advances, teachers are required to use technology (technology literacy) as a means (KBM). This demand is a problem for teachers, especially at SantaAngela Elementary School in Bandung.